2021
DOI: 10.1002/cpp.2608
|View full text |Cite
|
Sign up to set email alerts
|

Online psychological counselling during lockdown reduces anxiety symptoms and negative affect: Insights from Italian framework

Abstract: Several studies have shown how COrona VIrus Disease 2019 (COVID-19) and the consequent isolation and quarantine measures could affect physical and mental well-being. Therefore, the increased request for support and assistance represents a critical challenge for clinicians requiring a reorganization of care systems. In this regard, online counselling has been identified as a useful tool in providing psychological assistance and support. Thus, the main purpose of the current study was to investigate the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…A systematic review of mobile app-based college counseling services found preliminary evidence of efficacy of cognitive behavioral therapy on anxiety (Oliveira et al, 2021). Similarly, an Italian study of 53 subjects verified the versatility and usefulness of a single online counseling session in reducing state anxiety during the lockdown (Carbone et al, 2021). These findings are in line with the effect of counselor support on anxiety found in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…A systematic review of mobile app-based college counseling services found preliminary evidence of efficacy of cognitive behavioral therapy on anxiety (Oliveira et al, 2021). Similarly, an Italian study of 53 subjects verified the versatility and usefulness of a single online counseling session in reducing state anxiety during the lockdown (Carbone et al, 2021). These findings are in line with the effect of counselor support on anxiety found in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…The research investigating single-session interventions on mental health supported various psychological effects. For instance, a study examining online singlesession intervention psychological effects focused on psycho-education and anxiety management strategies showed that participants who received the intervention had a decrease in anxiety symptoms and negative affect, while there was no difference in positive affect and well-being [104]. The other single-session intervention study, which was designed to use behavioral activation, gratitude and cognitive restructuring techniques, revealed an increase in the well-being of the participants [103].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers who have studied the subject of online therapies found that one session intervention programs [103] as well as the other brief therapies/interventions [104] alleviated the psychological impact of the pandemic. These preliminary results are very promising.…”
Section: Protective Factors and Interventionsmentioning
confidence: 99%
“…Future career researchers and practitioners can try to combine the methods in LDC with art therapy methods such as painting, music, dance, and writing, so as to serve a more diverse group of individual or group clients. Last but not least, scholars may be able to conduct online and offline LDC through computers, mobile phones, telephones, and e-mails (Savarese et al, 2020;Carbone et al, 2021), and other flexible forms and combined with other emerging psychological counseling methods. In general, career practitioners need to create diversified LDC intervention methods in the future to help clients through narrative construction, deconstruction and joint construction of their personal career stories, find the core life theme, and carry out a meaningful life.…”
Section: Strengthen the Needs Analysis Of Clients And The Professional Training Of Counselors Of Life Design Counselingmentioning
confidence: 99%